CHALLENGES OF MADRASAH IBTIDA'IYAH IN INDONESIA IN BUILDING SCHOOL CULTURE IN THE ERA OF DIGITALIZATION - Siti Maryam Maryam; Ari Susetiyo Ari (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
This article explores the challenges faced by Madrasah Ibtida'iyah in Indonesia in building a school culture within the era of digitalization. As Islamic primary education institutions, Madrasah Ibtida'iyah play a crucial role in shaping students' moral and intellectual development, yet they encounter significant hurdles due to rapid technological advancements. Through a comprehensive literature review, the study identifies key challenges, including the integration of digital tools, teacher preparedness, resource limitations, and the preservation of Islamic values amidst digital distractions. Findings reveal that while digitalization offers opportunities for innovative learning, it also poses risks to traditional school culture, necessitating adaptive strategies. The discussion emphasizes the need for teacher training, curriculum adjustment, and community involvement to foster a balanced school culture. The study concludes with recommendations for policymakers and educators to navigate these challenges effectively, ensuring Madrasah Ibtida'iyah remain relevant in the digital age.